Composite positive electrode material and preparation method and application thereof

CN122977458APending Publication Date: 2026-10-27GEM WUXI ENERGY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611335039.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]本发明提供了一种复合正极材料及其制备方法和应用,以解决现有高镍层状正极材料改性技术难以兼顾低残碱含量、高结构稳定性与长循环性能的技术难题

Benefits of technology

1.本发明提供的复合正极材料的制备方法,通过在水洗阶段中引入含有氨基基团和羧基基团的络合剂以及调节预重构水洗液的pH为7.5-10.5,在高效去除表面残碱的同时,利用氨基和羧基与Ni2+的选择性配位络合作用,主动诱导高镍正极材料表面原位重构为高离子电导率的尖晶石相或有序缺锂层状结构,且该络合剂在材料表面形成的配位络合物层能够有效抑制水洗过程中的Li+/H+交换反应,减少电化学惰性NiO岩盐相的生成,从根源上解决传统水洗去残碱与稳定结构不可兼得的技术矛盾。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The application provides a composite positive electrode material and a preparation method and application thereof. The preparation method of the composite positive electrode material comprises the following steps: washing and sintering a high-nickel ternary positive electrode material by using a pre-reconstruction water washing solution to obtain the composite positive electrode material; the pH of the pre-reconstruction water washing solution is 7.5-10.5; and the pre-reconstruction water washing solution comprises a complexing agent. The preparation method of the composite positive electrode material provided by the application introduces a complexing agent in the water washing stage and adjusts the pH of the pre-reconstruction water washing solution to 7.5-10.5, so that the surface residual alkali is efficiently removed, the surface of the high-nickel positive electrode material is actively induced to be reconstructed into a spinel phase or an ordered lithium-deficient layered structure with high ionic conductivity in situ, and the coordination complex layer formed by the complexing agent on the surface of the material can effectively inhibit the Li + / H + exchange reaction in the water washing process, reduce the generation of electrochemically inert NiO rock salt phase, and fundamentally solve the technical contradiction that the traditional water washing residual alkali removal and structure stabilization cannot be compatible.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion batteries, specifically to a composite cathode material, its preparation method, and its application. Background Technology

[0002] High-nickel layered cathode materials possess an α-NaFeO2-type layered structure and a reversible specific capacity exceeding 200 mAh / g, making them the preferred cathode material for constructing next-generation high-energy-density lithium-ion batteries. However, this material faces several key technical challenges in practical applications: its surface residual alkali content (mainly LiOH and Li2CO3) is as high as several thousand ppm, easily leading to slurry gelation, battery gas generation, and a decrease in rate performance; simultaneously, the inherent Li... + / Ni 2+ The irreversible transformation of cation mixing and surface layered structure into electrochemically inert NiO rock salt phase significantly increases interfacial impedance. In addition, anisotropic lattice changes during charge and discharge lead to the generation of microcracks, which accelerates the degradation of the material structure. The release of lattice oxygen in the deep delithiation state further induces the risk of thermal runaway, which seriously restricts its large-scale application.

[0003] To address the aforementioned problems, existing technologies have proposed various modification schemes. Water washing can effectively reduce the residual alkali content on the surface; however, pure water washing inevitably triggers Li₂ oxidation. + / H + The exchange reaction leads to surface delithiation and instability of the layered structure, which in turn induces the formation of NiO rock salt phase and deteriorates the interfacial electrochemical performance. Existing improvement methods include ammonia-assisted washing, integrated washing and coating with organometallic coating agents, cyclodextrin-sodium metasilicate washing, and phosphate salt washing. However, these are essentially passive cleaning combined with coating and cannot effectively control the evolution of the surface structure during the washing process. In summary, the existing technology still has the following shortcomings: First, during the washing process, Li... + / H + The formation of NiO rock salt phase caused by exchange is difficult to suppress, resulting in the inability to control the negative effects on the surface structure of the cathode material, causing the problem of short battery cycle life; secondly, the existing solutions are all in the category of passive protection and have failed to achieve active regulation of the surface structure of the cathode material; thirdly, there is a contradiction between water washing time and residual alkali removal effect, and it is difficult to balance efficient alkali reduction and structural protection. Summary of the Invention

[0004] This invention provides a composite cathode material, its preparation method, and its application, in order to solve the technical problem that existing high-nickel layered cathode material modification technologies cannot simultaneously achieve low residual alkali content, high structural stability, and long cycle performance.

[0005] In a first aspect, the present invention provides a method for preparing a composite cathode material, comprising the following steps: washing and sintering a high-nickel ternary cathode material with a pre-reconstructed washing solution to obtain a composite cathode material; The pH of the pre-reconstructed washing solution is 7.5-10.5; The pre-reconstructed washing solution includes a complexing agent, which contains both amino and carboxyl groups.

[0006] In one optional embodiment, the solid-liquid ratio of the high-nickel ternary cathode material to the pre-reconstructed washing solution is 1 g: (1-5) mL; In one optional embodiment, the concentration of the complexing agent in the pre-reconstructed washing solution is 0.01-0.5 mol / L; In one optional embodiment, the preparation steps of the pre-reconstructed washing solution include heating water to 25-50°C, adding a complexing agent and a pH adjuster to control the pH value of the pre-reconstructed washing solution between 7.5 and 10.5.

[0007] In one optional embodiment, the sintering temperature is 300-600℃ and the sintering time is 2-10h; In one optional embodiment, the water washing step includes stirring at 250-450 rpm for 1-30 minutes at 20-50°C. In one optional embodiment, the water washing includes stirring at 250-450 rpm for 1-30 minutes at 20-50°C. In one optional embodiment, after washing the high-nickel ternary cathode material with water, before sintering, the high-nickel ternary cathode material is further subjected to a vacuum drying process at 80-150°C for 2-12 hours.

[0008] In one optional embodiment, the preparation method of the high-nickel ternary cathode material includes mixing a precursor and a lithium source, and calcining them to obtain the high-nickel ternary cathode material. Optionally, the ratio of the molar amount of Li in the lithium source to the total molar amount of transition metal ions in the precursor is (1.01-1.10):1; Optionally, the lithium source includes lithium hydroxide; Optionally, the precursor has the general chemical formula Ni. x Co y M 1-x-y (OH)2, where 0.80≤x≤0.98, 0.01≤y≤0.19, and M is at least one of Mn and Al; Optionally, the calcination temperature is 650-850℃, and the calcination time is 6-20h; Optionally, the step of mixing the precursor and the lithium source includes mixing the precursor and the lithium source at a speed of 300-800 rpm for 20-60 minutes.

[0009] In one optional embodiment, the method further includes the steps of mixing the obtained composite cathode material with a coating agent solution and calcining it. Optionally, the calcination temperature is 300-600℃, and the calcination time is 2-8 hours; Optionally, the total amount of coating agent added is 0.4-1.2% based on the mass of the composite cathode material; Optionally, the coating agent solution includes at least one of a first coating agent or a second coating agent, wherein the first coating agent includes a metal salt and the second coating agent includes at least one of boric acid and phosphate; Further optionally, the metal salt includes at least one of aluminum salt, titanium salt, and zirconium salt; the aluminum salt includes at least one of aluminum nitrate and aluminum isopropoxide; the titanium salt includes tetrabutyl titanate; and the zirconium salt includes zirconium n-butoxide. Further optionally, the phosphate includes at least one of ammonium dihydrogen phosphate and diammonium hydrogen phosphate; Optionally, the mass concentration of the coating agent solution is 0.5-5 wt%. Optionally, the step of mixing the obtained composite cathode material with the coating agent solution includes coating at 20-80°C and a rotation speed of 200-600 rpm for 30-120 min. Optionally, after mixing the obtained composite cathode material with the coating agent, the process further includes drying at 80-120°C for 2-6 hours before calcination.

[0010] In one optional embodiment, the complexing agent includes at least one of glycine, alanine, ethylenediaminetetraacetic acid (EDTA), and its EDTA ammonium salt. In one optional embodiment, the pH adjuster may include at least one of ammonia water and lithium hydroxide solution; Optionally, the mass concentration of the ammonia solution is 10-13 wt%. Optionally, the concentration of the lithium hydroxide solution is 0.1-2 mol / L; Understandably, the ammonia evaporates completely during subsequent sintering without introducing impurities; lithium hydroxide can also be used as a lithium source to replenish the lithium lost during the washing process.

[0011] Optionally, the mass ratio of the first coating agent and the second coating agent in the coating agent solution is (0.8-1.2):(0.8-1.2). In one optional embodiment, the solvent of the coating agent solution includes at least one of water and C1-C4 alcohol solvents; Optionally, the C1-C4 alcohol solvent includes at least one of ethanol and isopropanol.

[0012] Secondly, the present invention also provides a composite cathode material prepared by the above-described preparation method.

[0013] Thirdly, the present invention also provides a positive electrode sheet comprising the above-mentioned composite positive electrode material.

[0014] Fourthly, the present invention also provides a lithium-ion battery comprising the aforementioned composite cathode material.

[0015] Those skilled in the art will understand that the lithium-ion battery provided by the present invention may include structural components such as an electrolyte, a positive electrode, a negative electrode, a separator, and a casing. During the charging and discharging process, lithium ions repeatedly insert and extract between the positive and negative electrode. The electrolyte acts as a conductor between the positive and negative electrode. The separator is disposed between the positive and negative electrode, primarily to prevent short circuits between the positive and negative electrodes, while simultaneously allowing lithium ions to pass through.

[0016] As an example, the positive electrode sheet includes a positive current collector and a positive active layer. The positive current collector has two opposing surfaces in its own thickness direction, and the positive active layer is disposed on either or both of the opposing surfaces of the positive current collector. The material of the positive electrode sheet used in the lithium-ion battery of the present invention is a composite positive electrode material prepared by the preparation method provided by the present invention.

[0017] As an example, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer. The negative electrode current collector has two opposing surfaces in its own thickness direction, and the negative electrode active layer is disposed on either or both of the opposing surfaces of the negative electrode current collector. The materials, composition, and manufacturing methods of the negative electrode sheet used in the lithium-ion battery of the present invention may include any techniques disclosed in the prior art.

[0018] The material and shape of the separator used in the lithium-ion battery of the present invention are not particularly limited, and may include any technology disclosed in the prior art.

[0019] The electrolyte used in the lithium-ion battery of the present invention may also include any technology disclosed in the prior art.

[0020] This invention does not specifically limit the preparation method of lithium-ion batteries; lithium-ion batteries can be prepared using conventional preparation methods in the art. For example, positive electrode sheets, separators, and negative electrode sheets are stacked sequentially, with the separator located between the positive and negative electrode sheets. A cell is obtained through stacking or winding processes, and then the lithium-ion battery of this invention is obtained through baking, electrolyte injection, formation, and packaging.

[0021] Fifthly, the present invention provides an electrical device comprising the above-described lithium-ion battery.

[0022] It is understood that in the electrical equipment provided by the present invention, the lithium-ion battery can be used as a power source for the electrical equipment, or as an energy storage unit for the electrical equipment. The electrical equipment may be, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0023] Compared with the prior art, the present invention has the following beneficial effects: 1. The method for preparing the composite cathode material provided by this invention, by introducing a complexing agent containing amino and carboxyl groups during the water washing stage and adjusting the pH of the pre-reconstruction water washing solution to 7.5-10.5, efficiently removes residual alkali from the surface while utilizing the amino and carboxyl groups to react with Ni. 2+ The selective coordination complexation of the complexing agent actively induces the in-situ reconstruction of the surface of high-nickel cathode material into a spinel phase with high ionic conductivity or an ordered lithium-deficient layered structure. Furthermore, the coordination complex layer formed by the complexing agent on the material surface can effectively inhibit the Li+ / H+ exchange reaction during the water washing process and reduce the formation of electrochemically inert NiO rock salt phase, thus fundamentally solving the technical contradiction between the traditional water washing method of removing residual alkali and stabilizing the structure.

[0024] 2. The method for preparing the composite cathode material provided by this invention includes sintering at 300-600℃ for 2-10 hours, thereby constructing a two-step surface reconstruction locking process combining pre-reconstruction water washing and low-temperature heat treatment. After water washing, a low-temperature heat treatment at 300-600℃ is performed in an oxygen atmosphere to crystallize and order the metastable surface reconstruction layer formed during water washing, locking it into a stable functional structure—a spinel phase or an ordered lithium-deficient layered structure. Simultaneously, this low-temperature heat treatment step avoids further structural degradation that may be induced by high-temperature sintering and ensures the lattice coherence between the reconstruction layer and the substrate, allowing the surface functional structure to remain stable during subsequent high-temperature coating sintering and long-term electrochemical cycling. This transforms the water washing-induced in-situ reconstruction effect from a metastable state into a thermodynamically stable structural modification layer, achieving active and controllable locking of the surface structure evolution direction.

[0025] 3. The method for preparing composite cathode materials provided by this invention involves mixing and calcining with a coating agent solution. This is achieved through an integrated process chain of "pre-reconstruction water washing—sintering—coating—calcination," which synergistically completes water washing and alkali reduction, surface pre-reconstruction, and coating within the same process chain. Each step works in coordination and synergistically enhances the surface chemical composition, crystal structure, and interface characteristics, ultimately endowing the composite cathode material with low residual alkali content, high structural stability, and excellent cycle performance. Moreover, this method can be implemented on conventional water washing equipment without complex modifications, and it is low in cost and easy to scale up for industrial production.

[0026] 4. The method for preparing the composite cathode material provided by this invention includes a coating solution comprising a first coating agent and a second coating agent. In the composite coating layer thus constructed, the inner oxide-rich layer (alumina, titanium oxide, zirconium oxide, or a composite oxide thereof) provides structural stability and physical protection, effectively suppressing side reactions between the substrate and electrolyte during charging and discharging, and alleviating internal stress caused by anisotropic lattice changes; the outer fast ion-rich conductor layer (borate / phosphate group modified layer) provides a fast lithium-ion transport channel, significantly reducing interfacial impedance and avoiding the performance bottleneck of a single coating layer that cannot simultaneously achieve structural stability and ion transport due to its limited function. Simultaneously, this invention, through the distribution of the two coating components, forms a gradual interfacial transition region between the coating layer and the substrate, eliminating clear interfacial boundaries, effectively alleviating interfacial stress concentration caused by lattice parameter mismatch, and preventing coating layer peeling failure during long-term cycling, thereby endowing the material with excellent cycle stability and rate performance. Detailed Implementation

[0027] The following embodiments are provided to better understand the present invention, but the following embodiments do not constitute a limitation on the content and scope of protection of the present invention. Any product that is the same as or similar to the present invention, derived by any person under the guidance of the present invention or by combining the features of the present invention with other prior art, falls within the scope of protection of the present invention.

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having” and any variations thereof in the text of this application are intended to cover non-exclusive inclusion.

[0029] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0030] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers from a to b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed herein, and "0-5" is merely a shortened representation of these numerical combinations. Furthermore, when a parameter is described as an integer ≥ 2, it is equivalent to disclosing that the parameter can be, for example, integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0031] In the description of the embodiments of this application, the term "and / or" is merely a description of the relationship between related objects, indicating that there can be three relationships. For example, A and / or B can represent three situations: A exists alone, A and B exist simultaneously, and B exists alone.

[0032] In the description of the embodiments of this application, the term "at least one" refers to one or more (including two).

[0033] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0034] Unless otherwise specified, all experimental steps or conditions in the examples were performed according to conventional experimental procedures and conditions in the art. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0035] Example 1 This embodiment provides a composite cathode material, and the specific steps and operating parameters are as follows: S1, the precursor (Ni 0.8 Co 0.1 Mn 0.1 (OH)2) and lithium source (LiOH•H2O) were mixed in a high-speed mixer at 500 rpm for 30 min, and then placed in a tube furnace. Under an oxygen atmosphere (oxygen flow rate 100 mL / min, purity ≥99.5%), the temperature was increased to 750℃ at a rate of 5℃ / min and held for 10 h. After the holding period, the mixture was cooled to room temperature with the furnace, mechanically crushed, and passed through a 300-mesh sieve to obtain a high-nickel ternary cathode material. The ratio of the molar amount of Li in the lithium source to the total molar amount of transition metal ions in the precursor was 1.05:1.

[0036] S2, deionized water is heated to 35°C, and a complexing agent (glycine) is added to a concentration of 0.1 mol / L. The pH of the system is adjusted to 9.0 ± 0.2 with 12 wt% ammonia water to obtain the pre-reconstructed washing solution. The high-nickel ternary cathode material and the pre-reconstructed washing solution are mixed at a solid-liquid ratio of 1 g: 3 mL and stirred at 400 rpm for 10 min in a 35°C water bath. After washing, the mixture is vacuum filtered, and the filter cake is rinsed twice with a small amount of deionized water. The filter cake is placed in a vacuum drying oven and vacuum dried at 120°C for 6 h. The dried material is placed in a tube furnace and heated to 450°C at 3°C / min under an oxygen atmosphere and held for 6 h. The material is then cooled to room temperature with the furnace to obtain the composite cathode material. S3, aluminum nitrate and boric acid are dissolved in anhydrous ethanol at a mass ratio of 1:1 to obtain a coating agent with a total mass concentration of 3wt% for aluminum nitrate and boric acid; the composite cathode material is added to the coating agent, stirred for 30 min, filtered, placed in a tube furnace, heated to 450℃ at 3℃ / min under an oxygen atmosphere, held at that temperature for 4 h, cooled to room temperature with the furnace, and passed through a 300-mesh sieve to obtain the composite cathode material; the total amount of coating agent added is 0.8wt% based on the mass of the composite cathode material.

[0037] Example 2 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that: In step S2, deionized water is heated to 45°C, and a complexing agent (ethylenediaminetetraacetic acid) is added to a concentration of 0.05 mol / L. The pH of the system is adjusted to 8.5 ± 0.2 with 12 wt% ammonia water to obtain the pre-reconstructed washing solution. The high-nickel ternary cathode material and the pre-reconstructed washing solution are mixed at a solid-liquid ratio of 1 g: 4 mL and stirred at 300 rpm for 8 min in a 40°C water bath. After washing, the mixture is vacuum filtered.

[0038] Example 3 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that: In step S2, the dried material is placed in a tube furnace and heated to 500°C at 3°C / min in an oxygen atmosphere, held at that temperature for 4 hours, and then cooled to room temperature with the furnace. In step S3, the coated material is placed in a tube furnace and heated to 500°C at 3°C / min under an oxygen atmosphere, held at that temperature for 4 hours, cooled to room temperature with the furnace, and then passed through a 300-mesh sieve.

[0039] Example 4 This embodiment provides a composite cathode material, and the specific steps and operating parameters are as follows: S1, the precursor (Ni 0.8 Co 0.15 Al 0.05 (OH)2) and lithium source (LiOH•H2O) were mixed in a high-speed mixer at 500 rpm for 30 min, and then placed in a tube furnace. Under an oxygen atmosphere (oxygen flow rate 100 mL / min, purity ≥99.5%), the temperature was increased to 720℃ at a rate of 5℃ / min and held for 12 h. After the holding period, the mixture was cooled to room temperature with the furnace, mechanically crushed, and passed through a 300-mesh sieve to obtain a high-nickel ternary cathode material. The ratio of the molar amount of Li in the lithium source to the total molar amount of transition metal ions in the precursor was 1.06:1.

[0040] S2, deionized water is heated to 35°C, a complexing agent (alanine) is added to a concentration of 0.15 mol / L, and the pH of the system is adjusted to 9.2 ± 0.2 with 12 wt% ammonia water to obtain the pre-reconstructed washing solution; the high-nickel ternary cathode material and the pre-reconstructed washing solution are mixed at a solid-liquid ratio of 1 g: 3 mL, stirred at 400 rpm for 12 min in a 35°C water bath, and after washing, vacuum filtered. The filter cake is rinsed twice with a small amount of deionized water, and the filter cake is placed in a vacuum drying oven and vacuum dried at 120°C for 6 h. The dried material is placed in a tube furnace and heated to 480°C at 3°C / min under an oxygen atmosphere, held for 6 h, and cooled to room temperature with the furnace to obtain the composite cathode material; S3, aluminum nitrate and boric acid are dissolved in anhydrous ethanol at a mass ratio of 1:1 to obtain a coating agent with a total mass concentration of 3wt% for aluminum nitrate and boric acid; the composite cathode material is added to the coating agent, stirred for 30 min, filtered, placed in a tube furnace, heated to 480℃ at 3℃ / min under an oxygen atmosphere, held at that temperature for 4 h, cooled to room temperature with the furnace, and passed through a 300-mesh sieve to obtain the composite cathode material; the total amount of coating agent added is 0.8wt% based on the mass of the composite cathode material.

[0041] Example 5 This embodiment provides a composite cathode material, and the specific steps and operating parameters are as follows: S1, the precursor (Ni 0.95 Co 0.01 Mn 0.04 (OH)2) and lithium source (LiOH•H2O) were mixed in a high-speed mixer at 600 rpm for 40 min, and then placed in a tube furnace. Under an oxygen atmosphere (oxygen flow rate 100 mL / min, purity ≥99.5%), the temperature was increased to 700℃ at a heating rate of 5℃ / min and held for 15 h. After the holding period, the mixture was cooled to room temperature with the furnace, mechanically crushed, and passed through a 300-mesh sieve to obtain a high-nickel ternary cathode material. The ratio of the molar amount of Li in the lithium source to the total molar amount of transition metal ions in the precursor was 1.04:1.

[0042] S2, deionized water is heated to 40°C, and a complexing agent (glycine) is added to a concentration of 0.3 mol / L. The pH of the system is adjusted to 8 with 11 wt% ammonia water to obtain the pre-reconstructed washing solution. The high-nickel ternary cathode material and the pre-reconstructed washing solution are mixed at a solid-liquid ratio of 1 g: 4 mL and stirred at 400 rpm for 20 min in a 40°C water bath. After washing, the mixture is vacuum filtered, and the filter cake is rinsed twice with a small amount of deionized water. The filter cake is placed in a vacuum drying oven and vacuum dried at 100°C for 10 h. The dried material is placed in a tube furnace and heated to 400°C at 3°C / min under an oxygen atmosphere and held for 8 h. The material is then cooled to room temperature with the furnace to obtain the composite cathode material. S3, aluminum nitrate and boric acid are dissolved in anhydrous ethanol at a ratio of 1:1 to obtain a coating agent with a total mass concentration of 3 wt% for aluminum nitrate and boric acid; the composite cathode material is added to the coating agent, stirred for 30 min, filtered, placed in a tube furnace, heated to 400℃ at 3℃ / min and held for 6 h in an oxygen atmosphere, cooled to room temperature with the furnace, and passed through a 300-mesh sieve to obtain the composite cathode material; the total amount of coating agent added is 1.0 wt% based on the mass of the composite cathode material.

[0043] Example 6 This embodiment provides a composite cathode material, and the specific steps and operating parameters are as follows: S1, the precursor (Ni 0.80 Co 0.1 Mn 0.1(OH)2) and lithium source (LiOH•H2O) were mixed in a high-speed mixer at 300 rpm for 60 min, and then placed in a tube furnace. Under an oxygen atmosphere (oxygen flow rate 100 mL / min, purity ≥99.5%), the temperature was increased to 650℃ at a heating rate of 5℃ / min and held for 20 h. After the holding period, the mixture was cooled to room temperature with the furnace, mechanically crushed, and passed through a 300-mesh sieve to obtain a high-nickel ternary cathode material. The ratio of the molar amount of Li in the lithium source to the total molar amount of transition metal ions in the precursor was 1.01:1.

[0044] S2, deionized water is heated to 50°C, a complexing agent (alanine) is added to a concentration of 0.01 mol / L, and the pH of the system is adjusted to 7.5 with a 2 mol / L dilute lithium hydroxide solution to obtain the pre-reconstructed washing solution; the high-nickel ternary cathode material and the pre-reconstructed washing solution are mixed at a solid-liquid ratio of 1 g: 5 mL, stirred at 400 rpm for 30 min in a 20°C water bath, and after washing, vacuum filtered. The filter cake is rinsed twice with a small amount of deionized water, and the filter cake is placed in a vacuum drying oven and vacuum dried at 80°C for 12 h. The dried material is placed in a tube furnace and heated to 300°C at 3°C / min under an oxygen atmosphere and held for 10 h. The material is then cooled to room temperature with the furnace to obtain the composite cathode material. S3, aluminum isopropoxide and ammonium dihydrogen phosphate are dissolved in isopropanol at a ratio of 0.8:1.2 to obtain a coating agent with a concentration of 5wt%; the composite cathode material is added to the coating agent, stirred for 30 min, filtered, placed in a tube furnace, heated to 300℃ at 3℃ / min and held for 8 h in an oxygen atmosphere, cooled to room temperature with the furnace, and passed through a 300-mesh sieve to obtain the composite cathode material; the total amount of coating agent added is 0.4wt% based on the mass of the composite cathode material.

[0045] Example 7 This embodiment provides a composite cathode material, and the specific steps and operating parameters are as follows: S1, the precursor (Ni 0.98 Co 0.01 Mn 0.01 (OH)2) and lithium source (LiOH•H2O) were mixed in a high-speed mixer at 800 rpm for 20 min, and then placed in a tube furnace. Under an oxygen atmosphere (oxygen flow rate 100 mL / min, purity ≥99.5%), the temperature was increased to 850℃ at a heating rate of 5℃ / min and held for 6 h. After the holding period, the mixture was cooled to room temperature with the furnace, mechanically crushed, and passed through a 300-mesh sieve to obtain a high-nickel ternary cathode material. The ratio of the molar amount of Li in the lithium source to the total molar amount of transition metal ions in the precursor was 1.10:1.

[0046] S2, deionized water is heated to 25°C, and a complexing agent (glycine) is added to a concentration of 0.5 mol / L. The pH of the system is adjusted to 10.5 with 10 wt% ammonia water to obtain the pre-reconstructed washing solution. The high-nickel ternary cathode material and the pre-reconstructed washing solution are mixed at a solid-liquid ratio of 1 g: 1 mL and stirred at 400 rpm for 1 min in a 50°C water bath. After washing, the mixture is vacuum filtered. The filter cake is rinsed twice with a small amount of deionized water. The filter cake is placed in a vacuum drying oven and vacuum dried at 150°C for 2 h. The dried material is placed in a tube furnace and heated to 600°C at 3°C / min under an oxygen atmosphere and held for 2 h. The material is then cooled to room temperature with the furnace to obtain the composite cathode material. S3, tetrabutyl titanate and boric acid are dissolved in water at a ratio of 1.2:0.8 to obtain a coating agent with a concentration of 0.5wt%; the composite cathode material is added to the coating agent, stirred for 30 min, filtered, placed in a tube furnace, heated to 600℃ at 3℃ / min and held for 2 h in an oxygen atmosphere, cooled to room temperature with the furnace, and passed through a 300-mesh sieve to obtain the composite cathode material; the total amount of coating agent added is 1.2wt% based on the mass of the composite cathode material.

[0047] Example 8 This embodiment provides a composite cathode material, which differs from Embodiment 1 only in that step S3 is omitted, i.e., no coating is performed.

[0048] Comparative Example 1 This comparative example provides a composite cathode material, which differs from Example 1 only in that it is used directly as a cathode material without any processing.

[0049] Comparative Example 2 This comparative example provides a composite cathode material, which differs from Example 1 only in that it uses water for washing instead of a pre-reconstruction washing solution, and the washing parameters are different. The specific operation is as follows: In step S2, the high-nickel ternary cathode material and deionized water are mixed at a solid-liquid ratio of 1g:5mL and stirred at 400rpm for 2min in a 35℃ water bath. After washing with water, the mixture is vacuum filtered. The filter cake is rinsed twice with a small amount of deionized water and placed in a vacuum drying oven for vacuum drying at 100℃ for 10h.

[0050] Comparative Example 3 This comparative example provides a composite cathode material, which differs from Example 1 only in that it does not use a pre-reconstruction washing solution but instead uses sulfosalicylic acid with a concentration of 0.1 mol / L for washing.

[0051] Comparative Example 4 This comparative example provides a composite cathode material, which differs from Example 1 only in that the pH of the pre-reconstructed washing solution is 6.

[0052] Experimental Example 1 (1) Residual alkali content test The composite cathode materials obtained in Examples 1-8 and Comparative Examples 1-4 were dispersed in deionized water and stirred at 20 r / min for 30 min. The supernatant was then filtered. A calibrated hydrochloric acid solution of cmol / L was used as the titrant, with phenolphthalein and methyl orange as indicators. The volume of hydrochloric acid corresponding to the phenolphthalein endpoint (V1) and the total volume of hydrochloric acid corresponding to the methyl orange endpoint (V2) were recorded. The mass content of LiOH and Li2CO3 in the cathode material was calculated based on the dual-endpoint titration results, and the sum of the mass contents of LiOH and Li2CO3 was taken as the total residual alkali content.

[0053] The specific calculation formula is as follows: n(Li2CO3) = c × (V2 - V1); n(LiOH) = c × (2 × V1 - V2); w(Li2CO3)=c×(V2-V1)×M(Li2CO3)×10 -3 ×f / m×100%; w(LiOH)=c×(2×V1-V2)×M(LiOH)×10 -3 ×f / m×100%; w(total residual alkali) = w(LiOH) + w(Li2CO3); Where V1 = the volume of hydrochloric acid consumed at the phenolphthalein endpoint, in mL; V2 = Total volume of hydrochloric acid consumed at the methyl orange endpoint, in mL; c = concentration of standard hydrochloric acid solution, mol / L; m = sample mass, g; M(LiOH) = 23.95 g / mol; M(Li₂CO₃) = 73.89 g / mol; f = dilution factor. When all the filtrate is titrated directly, f = 1.

[0054] (2) Electrochemical performance testing The composite cathode materials provided in the various embodiments and comparative examples were applied to lithium-ion batteries, and then their electrical performance was tested.

[0055] The method for preparing the lithium-ion battery includes the following steps: The composite cathode materials prepared in the above embodiments or comparative examples were used as cathode active materials and were homogenized and coated with polyvinylidene fluoride (PVDF) and acetylene black in a ratio of 80:10:10, with the areal density controlled at 4 mg / cm³. 2 The electrode compaction density is 2 g / cm³. 3The electrode was fabricated using a lithium metal sheet as the counter electrode and a glass fiber separator. A 1 mol / L lithium hexafluorophosphate solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) (EC to DMC volume ratio of 1:1) was used as the electrolyte. The CR2032 coin cell was assembled in an argon-filled glove box and finally placed in the Blue Electric testing system for electrical performance testing.

[0056] The specific method for the electrical performance test is as follows: ① First charge-discharge performance test After the open-circuit voltage stabilizes at 25°C, the battery's first charge-discharge performance is tested by cycling at 0.1C / 0.1C for one week: the initial charge capacity is defined as the capacity when the battery is charged at a constant current of 0.1C until the voltage reaches 4.8V, and the initial discharge capacity is defined as the capacity when the battery is discharged at a constant current of 0.1C until the cutoff voltage reaches 2.0V. The first-cycle coulombic efficiency (first-cycle efficiency) is then calculated.

[0057] The coulomb efficiency for the first lap is calculated as follows: ; Where: ICE is the initial coulomb efficiency; D1 is the initial discharge capacity (mAh) at a specified rate (e.g., 0.1C). C1 represents the initial charge capacity (mAh) at the same charging rate.

[0058] The calculation method for 0.1C discharge specific capacity (mAh / g) is as follows: ; Where m is the mass (g) of the active material in the positive electrode.

[0059] ② Cyclic stability test The assembled coin cell was charged at a constant current of 1C to 4.8V and then discharged at a constant current of 1C until the cutoff voltage of 2.0V was reached. This process was repeated 203 times, and the cycle capacity retention rate of the battery after 203 cycles was calculated.

[0060] The cycle capacity retention rate (%) is calculated as follows: .

[0061] The specific test results are shown in the table below: Table 1 Electrical performance test data

[0062] The data above show that the residual alkali content of the composite cathode materials prepared in Examples 1-8 is 220-350 ppm, and the alkali reduction rate is 79.9%-87.4%, which is far superior to all comparative examples. Among them, Example 5 has the lowest residual alkali, mainly due to the synergistic effect of its high complexing agent concentration (0.3 mol / L glycine) and sufficient water washing time (20 min).

[0063] Compared to Example 1, the residual alkali content of the untreated material in Comparative Example 1 was as high as 1745 ppm, which is a typical value for the chemical instability of the surface of high-nickel ternary materials. After washing with pure water, the residual alkali content in Comparative Example 2 decreased to 820 ppm, with an alkali reduction rate of 53.0%. Although this showed some effect, washing with pure water could trigger Li... + / H + Exchange leads to surface structural instability and the formation of NiO rock salt phase; Comparative Example 3 uses a complexing agent without amino and carboxyl groups, and the residual alkali content is as high as 1100 ppm, indicating that amino and carboxyl groups interact with Ni. 2+ The selective coordination complexation of the compound plays a significant role in reducing residual alkali; in Comparative Example 4, the alkali was reduced to 650 ppm, which is better than washing with pure water, but the acidic environment exacerbated H exchange and surface damage.

[0064] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.

Claims

1. A method for preparing a composite cathode material, characterized in that, Includes the following steps: A composite cathode material was obtained by washing and sintering a high-nickel ternary cathode material with a pre-reconstruction washing solution. The pH of the pre-reconstructed washing solution is 7.5-10.5; The pre-reconstructed washing solution includes a complexing agent, which contains both amino and carboxyl groups.

2. The preparation method according to claim 1, characterized in that, The solid-liquid ratio of the high-nickel ternary cathode material to the pre-reconstructed washing solution is 1g:(1-5)mL; And / or, the concentration of the complexing agent in the pre-reconstructed washing solution is 0.01-0.5 mol / L; And / or, the preparation steps of the pre-reconstructed washing solution include heating water to 25-50°C, adding a complexing agent and a pH adjuster to control the pH value of the pre-reconstructed washing solution between 7.5 and 10.

5.

3. The preparation method according to claim 1 or 2, characterized in that, The sintering temperature is 300-600℃, and the sintering time is 2-10h; And / or, the water washing step includes stirring at 250-450 rpm for 1-30 minutes at 20-50°C; And / or, after washing the high-nickel ternary cathode material with water, before sintering, the process also includes a step of vacuum drying the high-nickel ternary cathode material at 80-150℃ for 2-12 hours.

4. The preparation method according to any one of claims 1-3, characterized in that, The preparation method of the high-nickel ternary cathode material includes mixing a precursor and a lithium source, and calcining them to obtain the high-nickel ternary cathode material. Optionally, the ratio of the molar amount of Li in the lithium source to the total molar amount of transition metal ions in the precursor is (1.01-1.10):1; Optionally, the lithium source includes lithium hydroxide; Optionally, the precursor has the general chemical formula Ni. x Co y M 1-x-y (OH)2, where 0.80≤x≤0.98, 0.01≤y≤0.19, and M is at least one of Mn and Al; Optionally, the calcination temperature is 650-850℃, and the calcination time is 6-20h; Optionally, the step of mixing the precursor and the lithium source includes mixing the precursor and the lithium source at a speed of 300-800 rpm for 20-60 minutes.

5. The preparation method according to claim 1, characterized in that, It also includes the steps of mixing the obtained composite cathode material with the coating agent solution and calcining it; Optionally, the calcination temperature is 300-600℃, and the calcination time is 2-8 hours; Optionally, the total amount of coating agent added is 0.4-1.2% based on the mass of the composite cathode material; Optionally, the coating agent solution includes at least one of a first coating agent and a second coating agent, wherein the first coating agent includes a metal salt and the second coating agent includes at least one of boric acid and phosphate; Optionally, the mass concentration of the coating agent in the coating agent solution is 0.5-5 wt%; Optionally, the step of mixing the obtained composite cathode material with the coating agent solution includes mixing at 20-80°C and a rotation speed of 200-600 rpm for 30-120 min; Optionally, after mixing the obtained composite cathode material with the coating agent, the process further includes drying at 80-120°C for 2-6 hours before calcination.

6. The preparation method according to any one of claims 1-5, wherein the complexing agent comprises at least one selected from glycine, alanine, ethylenediaminetetraacetic acid and its ammonium salt; And / or, the pH adjuster may include at least one of ammonia water and lithium hydroxide solution; Optionally, the mass concentration of the ammonia solution is 10-13 wt%. Optionally, the concentration of the lithium hydroxide solution is 0.1-2 mol / L; And / or, when the coating agent solution comprises a first coating agent and a second coating agent, the mass ratio of the first coating agent to the second coating agent is (0.8-1.2):(0.8-1.2). And / or, the solvent of the coating agent solution includes at least one of water and C1-C4 alcohol solvents.

7. A composite cathode material prepared by the preparation method according to any one of claims 1-6.

8. A positive electrode sheet comprising the composite positive electrode material as described in claim 7.

9. A lithium-ion battery, characterized in that, It includes the positive electrode sheet as described in claim 8.

10. An electrical appliance, characterized in that, It includes the lithium-ion battery as described in claim 9.